Low temperature kinetics and theoretical studies of the reaction CN + CH3NH2: a potential source of cyanamide and methyl cyanamide in the interstellar medium. Issue 8 (30th October 2017) - Sleiman, Chantal; El Dib, Gisèle; Rosi, Marzio; Skouteris, Dimitrios; Balucani, Nadia; Canosa, André
Abstract : Combined experimental/theoretical studies demonstrate that the reaction between cyano radicals and methylamine is an efficient formation route of interstellar cyanamide. Abstract : The reaction between cyano radicals (which are ubiquitous in interstellar clouds) and methylamine (a molecule detected in various interstellar sources) has been investigated in a synergistic experimental and theoretical study. The reaction has been found to be very fast in the entire range of temperatures investigated (23–297 K) by using a CRESU apparatus coupled to pulsed laser photolysis – laser induced fluorescence. The global experimental rate coefficient is given by In addition, dedicated electronic structure calculations of the underlying potential energy surface have been performed, together with capture theory and RRKM calculations. The experimental data have been interpreted in the light of the theoretical calculations and the product branching ratio has been established. According to the present study, in the range of temperatures investigated the title reaction is an efficient interstellar route of formation of cyanamide, NH2 CN, another interstellar species. The second most important channel is the one leading to methyl cyanamide, CH3 NHCN (an isomer of aminoacetonitrile), via a CN/H exchange mechanism with a yield of 12% of the global reaction in the entire range of temperatures explored. For a possible inclusion in future astrochemical models we suggest, by referring to the usual expression the following values: α = 3.68 × 10 −12 cm 3 molec −1 s −1, β = −1.80, γ = 7.79 K for the channel leading to NH2 CN + CH3 ; α = 5.05 × 10 −13 cm 3 molec −1 s −1, β = −1.82, γ = 7.93 K for the channel leading to CH3 NHCN + H.